Proximity and post-COVID-19 urban development: Reflections from Milan, Italy - Luca Tricarico; Lorenzo De Vidovich (Journal of Urban Management, 2021)
This paper aims to describe the impact of the COVID-19 pandemic on the socio-economic structure of cities, and discuss the possible responses of a place-based agenda of urban policies built around the concept of "proximity economy". With this objective, the present work provides an interpretative framework for understanding the impact on urban economy with respect to Milan and Italy, by observing the emergence of the perspective of proximity in the debate to respond to the healthcare crisis due to the current pandemic. On this conceptual basis, the paper suggests measures and gives examples for implementing a proximity-based urban development agenda, concluding with a final framework of policy recommendations relating to the implementation of these policies.
Keywords: 710; Urban economy; Urban development; Urban recovery; Proximity; Covid-19